Patterns and management of traumatic bowel perforation: insights from a single-center experience - Joshi, Varun; Patel, Ojas; Dave, Divyang; Astik, Hardik; Patel, Shraddha; Bansal, Nipun (International Surgery Journal, 2025)
Background: Trauma is a major cause of morbidity and mortality globally, with abdominal trauma ranking third in prevalence after head and chest injuries. Bowel perforations due to blunt or penetrating trauma pose significant diagnostic and therapeutic challenges, particularly in resource-constrained settings. Methods: This retrospective observational study was conducted at a tertiary care hospital in South Gujarat. Fifty patients with traumatic bowel perforations who underwent surgical management were included. Demographic data, mode and type of injury, clinical features, operative findings, and outcomes were analyzed. Results: The mean age was 30.4 years, with a male predominance (96%). Penetrating trauma (64%) was more common than blunt trauma (36%). The most common cause was assault (62%), followed by road traffic accidents (RTA) (26%). The ileum was the most frequently injured bowel segment. Surgical interventions included primary repair, resection and anastomosis, and stoma formation. Morbidity was primarily due to wound infections and intra-abdominal abscesses. Mortality was noted in 4% of cases. Conclusions: Early recognition and timely surgical intervention significantly reduce the morbidity and mortality associated with traumatic bowel perforations. A high index of suspicion and clinical acumen remain critical in the effective management of abdominal trauma.